2000
DOI: 10.1074/jbc.m909868199
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Cardiolipin in the crd1 Null Mutant Results in Decreased Mitochondrial Membrane Potential and Reduced Mitochondrial Function

Abstract: Cardiolipin (CL) is a unique phospholipid which is present throughout the eukaryotic kingdom and is localized in mitochondrial membranes. Saccharomyces cerevisiae cells containing a disruption of CRD1, the structural gene encoding CL synthase, have no CL in mitochondrial membranes. To elucidate the physiological role of CL, we compared mitochondrial functions in the crd1⌬ mutant and isogenic wild type. The crd1⌬ mutant loses viability at elevated temperature, and prolonged culture at 37°C leads to loss of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
387
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(414 citation statements)
references
References 55 publications
25
387
0
2
Order By: Relevance
“…The absence of CL in Dcls1 mitochondria would also be evidenced on whole cells by a cytofluorometric assay on spheroplasts stained with the CL-selective fluorescent probe nonyl acridine orange (NAO; Figure 1d, lower panel). A parallel staining of the cells with the mitochondrial membrane potential (DC m )-sensitive probe DiOC (6) 3 showed that the DC m was reduced, but not completely collapsed, in the Dcls1 strain (Figure 1d, upper panel), predicting that the bioenergetic capacity of Dcls1 mitochondria is moderately altered.…”
Section: Lipid Composition and Bioenergetic Characterization Of Dcls1mentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of CL in Dcls1 mitochondria would also be evidenced on whole cells by a cytofluorometric assay on spheroplasts stained with the CL-selective fluorescent probe nonyl acridine orange (NAO; Figure 1d, lower panel). A parallel staining of the cells with the mitochondrial membrane potential (DC m )-sensitive probe DiOC (6) 3 showed that the DC m was reduced, but not completely collapsed, in the Dcls1 strain (Figure 1d, upper panel), predicting that the bioenergetic capacity of Dcls1 mitochondria is moderately altered.…”
Section: Lipid Composition and Bioenergetic Characterization Of Dcls1mentioning
confidence: 99%
“…For DC m measurements, spheroplasts obtained from zymoliase treatment of the cells were incubated for 30 min in the presence of 5 nM DiOC (6) 3 in the absence or in the presence of 10 mM fluorocarbonyl cyanide m-chlorophenylhydrazone (FCCP), and fluorescence was detected at 530730 nm in the FL1 channel. For CLcontent measurements, spheroplasts were incubated for 30 min in the presence of 1 mM NAO and fluorescence was detected at 585740 nm in the FL2 channel.…”
Section: Flow Cytometry Measurements and Fluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…CL plays a key role in mitochondrial bioenergetics (Jiang et al, 2000; Greenberg, 2000, 2002;Schlame et al, 2000;Pfeiffer et al, 2003) and is also involved in mitochondrial biogenesis (Kawasaki et al, 1999;Jiang et al, 2000). Defective remodeling of CL is associated with Barth syndrome, a severe genetic disorder characterized by cardiomyopathy, neutropenia, skeletal myopathy, and respiratory chain defects (Vreken et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of PGS1, the structural gene encoding PGP synthase, results in the complete loss of both PG and CL (Janitor et al, 1996;Chang et al, 1998a). The crd1⌬ mutant, which lacks CL synthase, has no detectable CL but accumulates PG (Jiang et al, 1997;Chang et al, 1998b;Tuller et al, 1998;Jiang et al, 2000;Pfeiffer et al, 2003;Zhong et al, 2004). The human taffazin gene (TAZ1), which is associated with Barth syndrome, encodes a transacylase that may be involved in the remodeling of CL (Xu et al, 2003).…”
mentioning
confidence: 99%